The Influence of Ultraviolet Radiation, Ozonation, and Ultrasonic Field on the Effectiveness of Dye Removal from Aqueous Solutions - Małgorzata Kida; Sabina Ziembowicz (Applied Sciences)
This study presents an analysis of the effectiveness of the removal of three dyes, Indigo Carmine, Tartrazine, and Allura Red AC, using advanced oxidation methods. The research showed low efficiency in removing these dyes using acoustic waves. Neither the addition of hydrogen peroxide to assist the process nor increasing the intensity of the acoustic waves improved the degradation of the analyzed dyes. However, when ozone was applied, a 91% removal efficiency of Indigo Carmine was achieved after 30 min, while the other two dyes were resistant to degradation by ozone. The introduction of an additional amount of oxidant in the form of hydrogen peroxide and waste catalyst (steel shavings) resulted in an increased efficiency of removing all dyes and a shortening of the degradation process time. Ultraviolet radiation in the presence of a TiO2 catalyst was also effective only for Indigo Carmine. After 30 min, the removal efficiency of this dye reached 95%. It was also demonstrated that the catalyst dose affected the rate constant of the reaction. Kinetic studies revealed that the degradation of Indigo Carmine in an aqueous solution through advanced oxidation processes followed the first-order reaction kinetics. Energy demand calculations confirmed that the most effective Indigo Carmine removal process is the one using ozone with the addition of a catalyst and an oxidizer at pH = 3.